2017
DOI: 10.1177/2041669516686986
|View full text |Cite
|
Sign up to set email alerts
|

Touch Accelerates Visual Awareness

Abstract: To efficiently interact with the external environment, our nervous system combines information arising from different sensory modalities. Recent evidence suggests that cross-modal interactions can be automatic and even unconscious, reflecting the ecological relevance of cross-modal processing. Here, we use continuous flash suppression (CFS) to directly investigate whether haptic signals can interact with visual signals outside of visual awareness. We measured suppression durations of visual gratings rendered i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…Indeed, in line with the first prediction, a vast body of research has demonstrated that aware signals from one sensory modality thrust unaware signals in another sensory modality into perceptual awareness according to the classical multisensory principles of temporal coincidence, spatial concordance and semantic and phonological congruency 6 17 . With respect to the spatial ventriloquist illusion, we have recently demonstrated that a sound that we are aware of can boost a flash under dynamic flash suppression into perceptual awareness depending on audiovisual spatial congruency 18 .…”
Section: Introductionmentioning
confidence: 75%
“…Indeed, in line with the first prediction, a vast body of research has demonstrated that aware signals from one sensory modality thrust unaware signals in another sensory modality into perceptual awareness according to the classical multisensory principles of temporal coincidence, spatial concordance and semantic and phonological congruency 6 17 . With respect to the spatial ventriloquist illusion, we have recently demonstrated that a sound that we are aware of can boost a flash under dynamic flash suppression into perceptual awareness depending on audiovisual spatial congruency 18 .…”
Section: Introductionmentioning
confidence: 75%
“…As a matter of fact, we showed that the tactile acuity significantly predicts the misestimation of the proximo-distal dimension of body parts whereas it does not have an effect on the medio-lateral estimation. Multisensory representations of the body are formed in parietal cortex 35 and/or through interactions between unisensory processing centers: for example, it has been shown that visual information modulates somatosensory processing 36 and conversely, that somatosensory information affects visual processing 37 .…”
Section: Discussionmentioning
confidence: 99%
“…There have been several speculations on how multisensory integration occurs and subsequently resolves the given perceptual ambiguity to achieve unequivocal interpretation (Deroy, Spence, & Noppeney, 2016; Faivre, Filevich, Solovey, Kühn, & Blanke, 2018; Hsiao, Chen, Spence, & Yeh, 2012; Hu & Knill, 2010; Lunghi, Lo Verde, & Alais, 2017; Salomon et al., 2016; Salomon, Kaliuzhna, Herbelin, & Blanke, 2015; Salomon, Lim, Herbelin, Hesselmann, & Blanke, 2013; Shams & Beierholm, 2010; Smith, Grabowecky, & Suzuki, 2007). One of the highly plausible explanations is that some intrinsic commonality in one stimulus can bias the perception of the other stimulus.…”
Section: Discussionmentioning
confidence: 99%